2019
DOI: 10.1017/rdc.2019.95
|View full text |Cite
|
Sign up to set email alerts
|

Northeast Pacific Seawater Radiocarbon Recorded in Abalone Shells Obtained From Otsuchi Bay, Japan

Abstract: Reconstructing past ocean currents in the coastal regions is necessary to better understand the relationship between oceanographic changes and coastal ecosystems. It is known that variations have occurred with large-scale climate changes such as ENSO (El Niño Southern Oscillations) and PDO (Pacific Decadal Oscillations). Thus, reconstruction of past seawater conditions in coastal regions is needed to better understand the relationship between oceanographic changes and coastal ecosystems. Seawater radiocarbon i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In contrast, the subarctic current (Oyashio current) delivers water with low Δ 14 C values of ca. −50‰ (Ishikawa et al., 2021 ; Ota et al., 2021 ; Satoh et al., 2019 ). Therefore, a large geographic gradient of Δ 14 C (−50 to 50‰) appears in oceanic regions influenced by these two current systems.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the subarctic current (Oyashio current) delivers water with low Δ 14 C values of ca. −50‰ (Ishikawa et al., 2021 ; Ota et al., 2021 ; Satoh et al., 2019 ). Therefore, a large geographic gradient of Δ 14 C (−50 to 50‰) appears in oceanic regions influenced by these two current systems.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, radiocarbon (Δ 14 C) is a powerful tracer in seawater. Δ 14 C is a widely used tracer in a broad range of fields, including oceanography and fishery science (Ota et al, 2019;Larsen et al, 2018;Hirabayashi et al, 2017;Mitsuguchi et al, 2016;Kumamoto et al, 2013;Tsunogai et al, 1995). In the modern ocean, anthropogenic radiocarbon invades the natural carbon cycles (Ostlund and Stuiver, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Since radiocarbon reservoir ages reflect hydrosphere dynamics, there are many studies that consider changes in seawater radiocarbon in the ocean with time (e.g., Hirabayashi et al, 2017Hirabayashi et al, , 2019Ota et al, 2019;Servettaz et al, 2019). However, few systematic lake water reservoir age studies have been reported.…”
Section: Introductionmentioning
confidence: 99%